The impact of virtual tour on tourism: the role of virtual tourism in COVID-19 and the impact on on-site tourism - LI, YIGE (2022)
Purpose- The aim of this thesis is to investigate the relationship between virtual tourism experiences, virtual tourism revisit intentions and field tourism as influenced by the COVID-19. To aid in optimizing virtual tourism technology, understanding the present elements impacting traveler adoption of virtual tourism experience technology is essential. In addition, to investigate the extrinsic and intrinsic factors influencing the acceptance of virtual tourism technology by users. Finally, exploring the impact of virtual tourism technology under the epidemic on users' attitudes towards switching to field tourism is helpful to provide some insights into the recovery of a depressed tourism industry.